Excision of Tn10 from the donor site during transposition occurs by flush double-strand cleavages at the transposon termini. - Benjamin, H W (1992)
Tn10 transposition is accomplished without extensive replication of the transposon sequences. Replicative cointegrate formation is precluded by efficient separation of transposon sequences from flanking donor DNA at an early stage in the transposition reaction. We report here that excision of Tn10 from its donor site occurs by a pair of flush double-strand breaks. Breaks occur at each end of the element precisely between the terminal base pair of the element and the first base pair of flanking DNA. This observation provides definitive evidence that cleavage of both strands of the element occurs under the direct control of Tn10 transposase protein. It is highly likely that transposase itself is directly responsible for these cleavages. The implications of this possibility are discussed.